Implementation of an Open Source Based Augmented Reality Engine for Cloud Authoring Frameworks - Mangiarua, Nahuel Adiel (2019)
In recent years the technology around Augmented Reality has grown considerably, in particular, cloud based always online solutions. In this paper we present a pipeline model and sample implementation that shows how an Augmented Reality engine can be built by leveraging advances in open source algorithm implementations. We also show how such an engine can be effectively integrated with cloud authoring tools to take advantage of the network connectivity and its computing power without an always online requirement.